Productivity and profitability of maize-legume cropping systems under conservation agriculture among smallholder farmers in Malawi - Amos Robert Ngwira; Vernon Kabambe; Pacsu Simwaka; Kondwani Makoko; Kefasi Kamoyo (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2020)
A study was conducted from 2014 to 2017 in Malawi to elucidate the short-term effects of maize-legume intercropping and rotation systems under conservation agriculture (CA) and conventional tillage (CT) on crop productivity and profitability. Twelve farmers hosted on-farm trials per district, in three districts, with each farmer having six plots. The design of the study was randomised complete block design arranged in a split plot fashion with tillage as main plot and cropping systems as sub-plots, with each farmer acting as a replicate. CA had 1400 and 3200 kg ha−1 more maize grain yield in the second and third seasons, respectively compared with CT. In the first two seasons, CT had 310, 180 and 270 kg ha−1 more cowpea, soybean and pigeon pea grain yields in Salima, Mzimba and Mangochi districts, respectively, compared with CA. Similarly, CA had 1100 and 950 kg ha−1 more groundnut grain yields than CT in Salima and Mzimba districts in the second and third seasons, respectively. Over the three-year study period, partial land equivalent ratio for maize ranged from 0.78 to 1.24. Largest net returns were achieved by intercropping maize with pigeon pea in Mangochi and rotating maize and groundnut in Mzimba and Salima districts.